Fangirl - Rowell, Rainbow (New York : St. Martin's Griffin, 2013)
Cath struggles to survive on her own in her first year of college while avoiding a surly roommate, bonding with a handsome classmate who only wants to talk about words, and worrying about her fragile father.
Keywords: Groupies -- Juvenile fiction; College freshmen -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Authorship -- Juvenile fiction